Simulation Analysis of a Multiple-Vehicle, High-Speed Train Collision Using a Simplified Model - Suchao Xie; Weilin Yang; Ping Xu (Shock and Vibration)
To solve the problems associated with multiple-vehicle simulations of railway vehicles including large scale modelling, long computing time, low analysis efficiency, need for high performance computing, and large storage space, the middle part of the train where no plastic deformation occurs in the vehicle body was simplified using mass and beam elements. Comparative analysis of the collisions between a single railway vehicle (including head and intermediate vehicles before, and after, simplification) and a rigid wall showed that variations in impact kinetic energy, internal energy, and impact force (after simplification) are consistent with those of the unsimplified model. Meanwhile, the finite element model of a whole high-speed train was assembled based on the simplified single-vehicle model. The numbers of nodes and elements in the simplified finite element model of the whole train were 63.4% and 61.6%, respectively, compared to those of the unsimplified model. The simplified whole train model using the above method was more accurate than the multibody model. In comparison to the full-size finite element model, it is more specific, had more rapid computational speed, and saved a large amount of computational power and storage space. Finally, the velocity and acceleration data for every car were discussed through the analysis of the collision between two simplified trains at various speeds.